TOO CONSCIENTIOUS TO BE INNOVATIVE? DIGITAL LEADERSHIP AND EMPLOYEE SERVICE INNOVATIVE BEHAVIOR (Contemporary Journal of Social Science Review, 2025)
For any organization to restrict new activities and get an advantage over rivals via digital transformation, service innovative behavior is essential. Despite a considerable study on the relation between leadership and innovation service behavior, it is still unclear how digital leadership fosters innovative behavior. In this context, research looks at how conscientiousness influences the innovative behavior of frontline leadership and digital leadership in the hospitality sector. The upper echelon hypothesis supports this correlation. We evaluated the theoretical model in Malaysia's hotel industry. Our research has a three-wave design with a four-month break time-lagged design (N=370). According to the study's results, conscientiousness has a strong moderating influence on the relationship between service innovation behaviour and digital leadership. Regarding the boundary condition of employee conscientiousness, the research has important ramifications for applying the impact of digital leadership on crucial workers' outcomes. The study's limitations and future directions for further research are studied.